2017
DOI: 10.21037/jgo.2017.07.03
|View full text |Cite
|
Sign up to set email alerts
|

CT-based assessment of visceral adiposity and outcomes for esophageal adenocarcinoma

Abstract: Background: Various methods of quantifying and correlating obesity to outcomes for patients with esophageal adenocarcinoma (EA) have been evaluated. Published data suggest that quantification of adiposity may be more accurate than body mass index (BMI) as a prognostic factor. We report our analysis of adiposity as a prognostic factor in a series of patients with EA. to −130. Outcomes were analyzed using Kaplan-Meier method and log-rank analysis. Multivariate analysis (MVA) was performed using the Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Sarcopenic obesity however be associated with adverse survival outcomes among patients with esophageal cancer (156). For VA specifically, a solitary study of 126 patients assessed its impact on survival among patients with EAC and reported no impact of visceral obesity above a median, but worsened outcomes with increasing visceral obesity presented in quartiles, principally due to more advanced clinical stage (157).…”
Section: Survivalmentioning
confidence: 99%
“…Sarcopenic obesity however be associated with adverse survival outcomes among patients with esophageal cancer (156). For VA specifically, a solitary study of 126 patients assessed its impact on survival among patients with EAC and reported no impact of visceral obesity above a median, but worsened outcomes with increasing visceral obesity presented in quartiles, principally due to more advanced clinical stage (157).…”
Section: Survivalmentioning
confidence: 99%
“…16 Both sarcopenia and obesity are associated with post-operative morbidity, mortality, and lower overall survival in patients with oesophageal cancer, and it is hypothesized that sarcopenic obesity may have a greater impact than either sarcopenia or obesity alone. [17][18][19][20] It is therefore of importance to evaluate influence of sarcopenia in combination with other body composition parameters and muscle strength on long-term and short-term outcomes in oesophageal cancer patients.…”
Section: Introductionmentioning
confidence: 99%